2015
DOI: 10.1016/j.amjcard.2015.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Impact of Co-morbidity Burden as Defined by the Charlson Co-morbidity Index on 30-Day and 1- and 5-Year Outcomes After Coronary Stent Implantation (from the Nobori-2 Study)

Abstract: Co-morbidities have typically been considered as prevalent cardiovascular risk factors and cardiovascular diseases rather than systematic measures of general co-morbidity burden in patients who underwent percutaneous coronary intervention (PCI). Charlson co-morbidity index (CCI) is a measure of co-morbidity burden providing a means of quantifying the prognostic impact of 22 co-morbid conditions on the basis of their number and prognostic impact. The study evaluated the impact of the CCI on cardiac mortality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

9
0

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 28 publications
2
35
0
1
Order By: Relevance
“…Capture of a wide range of comorbid conditions enabling calculation of comorbid burden through the CCI score in the NIS represented a robust objective attempt for comorbidity analysis, although frailty, per se, that is known to associate with poorer outcomes is not captured in this dataset, and is likely to be more prevalent in females who were on average 5 years older than men. Whilst the Charlson score is the most widely used measure of comorbid burden in the literature and has been shown to have an independent prognostic impact on both in-hospital and post discharge outcomes [33], systematic differences in comorbid prevalence between men and women not captured by the Charlson score may bias outcomes. Previous work has suggested that women are less likely to be offered invasive therapy in acute coronary syndromes than men [34] which may lead to imbalances in the risk profile of patients particularly in the ACS setting.…”
Section: Discussionmentioning
confidence: 99%
“…Capture of a wide range of comorbid conditions enabling calculation of comorbid burden through the CCI score in the NIS represented a robust objective attempt for comorbidity analysis, although frailty, per se, that is known to associate with poorer outcomes is not captured in this dataset, and is likely to be more prevalent in females who were on average 5 years older than men. Whilst the Charlson score is the most widely used measure of comorbid burden in the literature and has been shown to have an independent prognostic impact on both in-hospital and post discharge outcomes [33], systematic differences in comorbid prevalence between men and women not captured by the Charlson score may bias outcomes. Previous work has suggested that women are less likely to be offered invasive therapy in acute coronary syndromes than men [34] which may lead to imbalances in the risk profile of patients particularly in the ACS setting.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many of the co-morbidities used in the development of CPMs are cardiovascular risk factors, with important non-cardiovascular co-morbidities not considered 30 . In particular, frailty is not reflected in many of the CPMs, despite being particularly prevalent in elderly patients with aortic stenosis and previous work suggesting frailty to be associated with poor TAVI outcomes 31., 32..…”
Section: Discussionmentioning
confidence: 99%
“…Finally anaemia may merely be a marker of a greater co-morbid in frailer patients, and the statistical models may have been affected by incomplete adjustments for confounders such as co-morbid burden or frailty. Our previous work has shown that co-morbidity burden is significant in patients undergoing PCI and is independently associated with adverse shorter and longer-term clinical outcomes (35).…”
Section: Discussionmentioning
confidence: 99%